Análisis del cumplimiento y eficacia de La ordenanza para la gestión integral de residuos sólidos y desechos líquidos (aceites de cocina usado) en el cantón Montufar en el periodo 2021-2022 - Lucero Pozo, Melany Jessenia (2023)
The objective of this research is to analyze the compliance and effectiveness of the solid waste management ordinance of Montufar, Carchi Province, in the period 2021-2022, which is called Ordinance for the integrated management of solid waste and liquid waste (cooking oils) in the canton of Montufar. Starting from the question: Is the ordinance for the integrated management of solid waste issued by the Montufar Canton being complied with? The method used was the socio-legal one, which allowed determining the compliance with the ordinance under study and the social reality regarding its compliance, using documentary analysis techniques and interviews with certain people, including officials of the Municipal Government of Montufar, members of the Association of Collectors and citizens. The result was that there is no effective enforcement of the ordinance, considering the lack of knowledge on the part of citizens, and weak application of sanctions.